Photoresponse type covalent organic framework material as well as preparation method and application thereof
By preparing covalent organic framework material COFs with a porous structure and introducing amidoxime groups and porphyrin groups, the problems of low adsorption capacity and efficiency of existing adsorption materials in the treatment of low-concentration uranium solution are solved, and efficient and economical uranium extraction effect is achieved.
Patent Information
- Application Number
- CN202411735808.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
When treating low-concentration uranium solutions, existing adsorption capacity and efficiency are low, and their kinetic performance is slow, making it difficult to effectively apply in dynamic wastewater treatment.
Covalent organic framework material COFs are prepared by using metallized aldehyde porphyrin and 1,4-benzene diacetonitrile as matrix, and the introduction of amidoxime groups is improved to improve the affinity and selectivity for uranium ions, while forming photocatalytic capabilities through porphyrin groups, achieving the dual functions of adsorption and photocatalysis.
It significantly improves the adsorption capacity and extraction efficiency of uranium, can maintain good adsorption performance in multiple cycles, and has good regeneration and long-term stability.
Smart Images

Figure CN119529211A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nuclear pollutant treatment, and in particular to a light-responsive covalent organic framework material and a preparation method and application thereof. Background Art
[0002] As a key resource for nuclear energy, uranium plays an important role in the nuclear fuel cycle and related industries. However, global uranium resources are unevenly distributed, and the mining cost and environmental pressure of terrestrial uranium mines are increasing. Therefore, how to extract uranium from resources such as low-concentration uranium-containing wastewater and seawater has become one of the research hotspots. In particular, the uranium pollution problem in industrial wastewater not only poses a threat to the ecological environment and human health, but also causes a waste of resources. The development of efficient, economical and environmentally friendly uranium extraction technology is of great significance to resource recovery and environmental governance.
[0003] At present, the main methods for treating uranium-containing wastewater include chemical precipitation, solvent extraction, ion exchange and adsorption. Among them, adsorption has become the mainstream technology due to its low cost, simple operation and environmental friendliness. In recent years, with the development of materials science, a variety of adsorbent materials have been applied to uranium extraction research, such as nanomaterials, metal organic frameworks, covalent organic frameworks, etc. However, the adsorption method also has some problems. Although the above-mentioned adsorbent materials have improved the selectivity and adsorption capacity of uranium through functional design, they still face some technical bottlenecks: the adsorption method has limited treatment effect on low-concentration uranium solutions with a concentration below 50 ppm, and it is difficult to further increase the capture of uranium. The kinetic performance of most adsorbent materials is slow, which limits their application in dynamic wastewater treatment. The selectivity of existing adsorbent materials for uranium is interfered by other competitive ions, especially in complex water environments, and the efficiency of uranium extraction is low.
[0004] For example, the patent with application publication number CN115894830A discloses the preparation and application of an adsorption-photocatalytic covalent organic framework material. The adsorption-synergistic photocatalytic organic covalent material disclosed in the patent constructs a system integrating adsorption and photocatalysis, through which uranium (U(VI)) is adsorbed and catalyzed to reduce dissolved uranium U(VI) to insoluble uranium (U(IV)), thereby releasing new active sites to capture more uranium. Although the organic covalent material provided by the patent can improve the ability to extract uranium from wastewater to a certain extent, the uranium extraction ability of the material is limited by the release of uranium U(VI) from the active site, that is, limited by the catalytic efficiency of photogenerated electrons, and there is still a problem of low uranium adsorption capacity and efficiency. Summary of the invention
[0005] The existing materials have low capacity and efficiency for uranium adsorption. In order to solve the above technical problems, the present invention provides a photoresponsive covalent organic framework material and its preparation method and application. The present invention prepares a covalent organic framework material COFs with a porous structure by using metallized aldehyde porphyrin and 1,4-phenylenediacetonitrile as a matrix to achieve its strong adsorption capacity, and introduces amidoxime groups into the COFs material through a specific chemical reaction to improve the affinity and selectivity for uranyl and other uranium ions. At the same time, by using porphyrin groups as the covalent organic framework matrix of the COFs material, the catalytic ability of photocatalytically dissolved U(VI) to reduce to insoluble U(IV) is formed, that is, the dual functions of photocatalysis and adsorption are combined, so that the photoresponsive covalent organic framework material can release active sites based on catalytic conditions, thereby improving the ability to enrich U(VI) and improve the capacity of uranium adsorption.
[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing a photoresponsive covalent organic framework material, comprising the following steps: Step S1: reacting aldehyde porphyrin with a metal salt to obtain a metallated aldehyde porphyrin; Step S2: condensing the metallated aldehyde porphyrin with 1,4-benzenediacetonitrile to obtain a metal porphyrin covalent organic framework; Step S3: subjecting the metal porphyrin covalent organic framework to amidoximation reaction to obtain a photoresponsive covalent organic framework material.
[0007] The method of the present invention uses metallized aldehyde porphyrin and 1,4-phenylenediacetonitrile as a matrix to prepare a covalent organic framework material COFs with a porous structure. The covalent organic framework material has a large adsorption capacity, and introduces amidoxime groups into the COFs material through a specific chemical reaction to improve the affinity and selectivity for uranyl and other uranium ions. At the same time, by using the porphyrin group as the covalent organic framework matrix of the COFs material, the catalytic ability of reducing photocatalytically dissolved U(VI) to insoluble U(IV) is formed, that is, the dual functions of photocatalysis and adsorption are combined, so that the light-responsive covalent organic framework material can release active sites based on catalytic conditions, thereby improving the ability to enrich U(VI) and the capacity of uranium adsorption.
[0008] As a preferred embodiment of the above preparation method, in step S1, the aldehyde porphyrin is a porphyrin derivative having an aldehyde group.
[0009] As a preferred embodiment of the above preparation method, in step S1, the metal salt is a copper salt and / or a nickel salt.
[0010] The aldehyde porphyrin is regulated by metallization, and the d orbital of copper (Cu) or nickel (Ni) metal interacts with the π electron system of the porphyrin ring, which can effectively promote the separation of charge carriers and improve the photocatalytic activity of the material. At the same time, copper or nickel metallized porphyrin can enhance its catalytic adsorption ability under dark conditions. Therefore, the metal salt is preferably a copper salt or / and a nickel salt.
[0011] In addition, copper and nickel have strong affinity in porphyrin coordination chemistry and can promote the stabilization of metal ions through coordination. The metallated porphyrin complexes have unique advantages in applications such as catalysis.
[0012] As a preferred embodiment of the above preparation method, in step S1, the reaction is carried out under an inert gas atmosphere at a reaction temperature of 100-130°C.
[0013] The metalation of aldehyde porphyrin is carried out at a high temperature of 100-130°C, and an inert gas atmosphere is used for protection. The temperature of 100-130°C helps to promote the coordination reaction between metal ions and porphyrin rings, ensuring the efficient and effective progress of the reaction. The inert environment can effectively avoid the interference of oxygen, prevent oxidation reactions from occurring, and ensure the purity of the reaction and the stability of the metallized product.
[0014] As a preferred embodiment of the above preparation method, in step S2, the condensation reaction is carried out under solvent and catalyst conditions, the solvent is 1,2-dichlorobenzene, and the catalyst is an alkaline catalyst.
[0015] The high boiling point of 1,2-dichlorobenzene helps to provide a stable reaction environment at higher temperatures, dissolve the reactants, promote uniform contact between molecules, and avoid the occurrence of side reactions.
[0016] The base catalyst can significantly improve the efficiency of the Knoevenagel condensation reaction and avoid the occurrence of side reactions, thereby ensuring high purity and high yield of the target product. The base catalyst is preferably DBU (1,8-diazabicyclo[5.4.0]undec-7-ene).
[0017] As a preferred embodiment of the above preparation method, in step S3, the metal porphyrin covalent organic framework is subjected to amidoximation reaction with hydroxylamine.
[0018] As a preferred embodiment of the above preparation method, in step S3, the temperature of the amidoximation reaction is 80-100° C., and the reaction time is 20-30 hours.
[0019] The amidoximation reaction of the metal porphyrin covalent organic framework of the present invention needs to be carried out at a relatively high temperature of 80 to 100° C. to enable the metal porphyrin covalent organic framework to achieve amidoximation modification. The temperature cannot be too high, otherwise the high temperature will cause damage to the framework material structure and there will be problems with the completeness of the reaction; the temperature cannot be too low, otherwise the efficiency of the target reaction will be low and the side reactions will increase.
[0020] As a preferred embodiment of the above preparation method, in step S3, the catalyst for the amidoximation reaction is triethylamine.
[0021] Using triethylamine as a catalyst in the reaction can provide a suitable alkaline environment for the amidoximation reaction, which helps hydroxylamine to exert its nucleophilicity in the reaction and accelerate the conversion of aldehyde groups to amidoxime groups. The alkaline conditions of triethylamine can avoid the destruction of the COF structure by excessive alkalinity, and can ensure the high efficiency and selectivity of the reaction.
[0022] In a second aspect, the present invention provides a photoresponsive covalent organic framework material.
[0023] In a third aspect, the present invention provides the use of the photoresponsive covalent organic framework material prepared by the above preparation method in uranium extraction.
[0024] Compared with the prior art, the present invention has the following technical effects: (1) The photoresponsive covalent organic framework material provided by the present invention has a porous structure of COFs and has a large adsorption capacity. The amidoxime group is introduced into the COFs material through a specific chemical reaction to improve the affinity and selectivity for uranyl and other uranium ions. At the same time, by using the porphyrin group as the covalent organic framework matrix of the COFs material, the catalytic ability of photocatalytically dissolving U(VI) to reduce to insoluble U(IV) is formed. That is, the dual functions of photocatalysis and adsorption are combined, so that the photoresponsive covalent organic framework material can release active sites based on catalytic conditions, thereby improving the ability to enrich U(VI) and increase the uranium adsorption capacity.
[0025] (2) The photoresponsive covalent organic framework material provided by the present invention achieves the regulation of the photocatalytic performance of the photoresponsive covalent organic framework material by copper metal and nickel metal, so that the material expands the catalytic conditions for reducing U(VI) to insoluble U(IV), and can also achieve the reduction catalysis of U(VI) under dark conditions. That is, the reduction catalytic ability of the photoresponsive covalent organic framework material to U(VI) is effectively improved by copper metal and nickel metal, thereby greatly improving the uranium adsorption capacity of the photoresponsive covalent organic framework material. Compared with the existing adsorption-photocatalytic system, the organic framework material is less affected by the limitation of photogenerated carriers.
[0026] (3) The light-responsive covalent organic framework material provided by the present invention can maintain good adsorption performance in multiple cycles and can remove adsorbed uranium ions through a simple washing step. It has good regeneration and long-term stability, reduces the generation of waste, and conforms to the concept of green environmental protection. In addition, the adsorption light-responsive metal porphyrin COF material provided by the present invention is not only suitable for the treatment of low-concentration uranium-containing wastewater, but can also be extended to the extraction and utilization of uranium in seawater, and has important application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a reaction flow chart of Example 1 of the present invention; Figure 2 The H-NMR spectrum and C-NMR spectrum of aldehyde porphyrin; Figure 3 The H-NMR spectrum and C-NMR spectrum of metallized nickel porphyrin; Figure 4 This is a reaction flow chart of Example 2 of the present invention; Figure 5 X-ray diffraction spectra of Ni-Por-COF and Cu-Por-COF; Figure 6 The transient photocurrent diagram and Mott-Schottky curve diagram of Por-COF, Ni-Por-COF and Cu-Por-COF, wherein the left diagram is the transient photocurrent diagram and the right diagram is the Mott-Schottky curve diagram; Figure 7 The results of the determination of uranium extraction capacity of Por-COF, Ni-Por-COF and Cu-Por-COF under dark and light conditions are shown in the figure; Figure 8 This is a schematic diagram of the application of the photoresponsive covalent organic framework material provided by the present invention in the treatment of low-concentration uranium-containing wastewater. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a photoresponsive covalent organic framework material, comprising the following steps: Step S1: reacting aldehyde porphyrin with a metal salt to obtain a metallated aldehyde porphyrin; Step S2: condensing the metallated aldehyde porphyrin with 1,4-benzenediacetonitrile to obtain a metal porphyrin covalent organic framework; Step S3: subjecting the metal porphyrin covalent organic framework to amidoximation reaction to obtain a photoresponsive covalent organic framework material.
[0029] The present invention uses metallated aldehyde porphyrin and 1,4-benzenediacetonitrile as a matrix to prepare a covalent organic framework material COFs with a porous structure. The covalent organic framework material has a large adsorption capacity, and introduces amidoxime groups into the COFs material through a specific chemical reaction to improve the affinity and selectivity for uranyl and other uranium ions. At the same time, by using the porphyrin group as the covalent organic framework matrix of the COFs material, the catalytic ability of reducing photocatalytically dissolved U(VI) to insoluble U(IV) is formed, that is, the dual functions of photocatalysis and adsorption are combined, so that the light-responsive covalent organic framework material can release active sites based on catalytic conditions, thereby improving the ability to enrich U(VI) and the capacity of uranium adsorption.
[0030] As a preferred embodiment of the above preparation method, in step S1, the aldehyde porphyrin is a porphyrin derivative having an aldehyde group.
[0031] Specifically, the aldehyde porphyrin can be prepared by following steps one to three: Step 1: dissolving neopentyl glycol, p-phthalaldehyde and p-toluenesulfonic acid monohydrate in toluene, and then reacting under reflux with stirring in a N2 atmosphere; then purifying by column chromatography with a mixed solvent of ethyl acetate / petroleum ether to obtain a white product.
[0032] Step 2: Under N2 atmosphere, add the white product of step 1 and pyrrole to dry dichloromethane, then add trifluoroacetic acid and stir to mix; then add tetrachlorobenzoquinone, stir the reaction mixture (protected from light) under N2 atmosphere and room temperature to react; after the reaction is completed, perform rotary evaporation and purify by dichloromethane column chromatography to obtain a purple product.
[0033] Step 3: Dissolve the purple product of step 2 in chloroform, then add TFA, stir the reaction at room temperature for a period of time, use a saturated solution of K2CO3 to adjust the pH value of the mixture to 4.5~5.5 and stir the reaction, wash the crude product with water, then separate, take the organic phase and dry it with anhydrous Na2SO4, rotary evaporate, wash with methanol and filter to obtain a dark purple aldehyde porphyrin.
[0034] As a preferred embodiment of the above preparation method, in step S1, the metal salt is a copper salt and / or a nickel salt.
[0035] The aldehyde porphyrin is regulated by metallization, and the d orbital of copper (Cu) or nickel (Ni) metal interacts with the π electron system of the porphyrin ring, which can effectively promote the separation of charge carriers and improve the photocatalytic activity of the material. At the same time, copper or nickel metallized porphyrin can enhance its catalytic adsorption ability under dark conditions. Therefore, the metal salt is preferably a copper salt or / and a nickel salt.
[0036] In addition, copper and nickel have strong affinity in porphyrin coordination chemistry and can promote the stabilization of metal ions through coordination. The metallated porphyrin complexes have unique advantages in applications such as catalysis.
[0037] As a preferred embodiment of the above preparation method, in step S1, the reaction is carried out under an inert gas atmosphere at a reaction temperature of 100-130°C.
[0038] The metalation of aldehyde porphyrin is carried out at a high temperature of 100-130°C, and an inert gas atmosphere is used for protection. The temperature of 100-130°C helps to promote the coordination reaction between metal ions and porphyrin rings, ensuring the efficient and effective progress of the reaction. The inert environment can effectively avoid the interference of oxygen, prevent oxidation reactions from occurring, and ensure the purity of the reaction and the stability of the metallized product.
[0039] As a preferred embodiment of the above preparation method, in step S2, the condensation reaction is carried out under solvent and catalyst conditions, the solvent is 1,2-dichlorobenzene, and the catalyst is an alkaline catalyst.
[0040] The high boiling point of 1,2-dichlorobenzene helps to provide a stable reaction environment at higher temperatures, dissolve the reactants, promote uniform contact between molecules, and avoid the occurrence of side reactions.
[0041] The base catalyst can significantly improve the efficiency of the Knoevenagel condensation reaction and avoid the occurrence of side reactions, thereby ensuring high purity and high yield of the target product. The base catalyst is preferably DBU (1,8-diazabicyclo[5.4.0]undec-7-ene).
[0042] As a preferred embodiment of the above preparation method, in step S3, the metal porphyrin covalent organic framework is subjected to amidoximation reaction with hydroxylamine.
[0043] As a preferred embodiment of the above preparation method, in step S3, the temperature of the amidoximation reaction is 80-100° C., and the reaction time is 20-30 hours.
[0044] The amidoximation reaction of the metal porphyrin covalent organic framework of the present invention needs to be carried out at a relatively high temperature of 80 to 100° C. to enable the metal porphyrin covalent organic framework to achieve amidoximation modification. The temperature cannot be too high, otherwise the high temperature will cause damage to the framework material structure and there will be problems with the completeness of the reaction; the temperature cannot be too low, otherwise the efficiency of the target reaction will be low and the side reactions will increase.
[0045] As a preferred embodiment of the above preparation method, in step S3, the catalyst for the amidoximation reaction is triethylamine.
[0046] Using triethylamine as a catalyst in the reaction can provide a suitable alkaline environment for the amidoximation reaction, which helps hydroxylamine to exert its nucleophilicity in the reaction and accelerate the conversion of aldehyde groups to amidoxime groups. The alkaline conditions of triethylamine can avoid the destruction of the COF structure by excessive alkalinity, and can ensure the high efficiency and selectivity of the reaction.
[0047] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.
[0048] Example 1 This embodiment provides a photoresponsive covalent organic framework material, and its preparation process is as follows: Figure 1 As shown, the preparation is carried out according to the following steps 1 to 4: Step 1: Preparation of aldehyde porphyrin Neopentyl glycol (8.5 g, 82 mmol), p-phthalaldehyde (10.9 g, 82 mmol) and p-toluenesulfonic acid monohydrate (TsOH, 50 mg, 0.3 mmol) were dissolved in 100 mL of toluene in a round-bottom flask (volume 250 mL), and then refluxed for 23 h under stirring and N2 atmosphere. The reaction was monitored by thin layer chromatography (TLC); then purified by column chromatography with ethyl acetate / petroleum ether (v / v, 1 / 10) to obtain a white product. Under N2 atmosphere, add the white product (6.74 g, 30.6 mmol) and pyrrole (2.8 mL) to dry dichloromethane (720 mL), then add trifluoroacetic acid (TFA, 1.9 mL) and stir for 60 min; then add tetrachlorobenzoquinone (3.92 g, 15.9 mmol), stir for 14 h at room temperature and N2 atmosphere in the dark, and monitor the reaction by TLC; then add triethylamine (1 ml) dropwise to quench the reaction and stir for 30 min, rotary evaporate, and purify by dichloromethane column chromatography to obtain a purple product. Step 3: Dissolve the purple product (378 mg, 0.35 mmol) of step 2 in chloroform (CHCl3, 40 mL). After adding TFA (18 mL), stir the resulting solution at room temperature overnight, and monitor the reaction by TLC. The pH value of the mixture was adjusted to 5.0 using a saturated solution of K2CO3 and stirred for 4 hours, then the crude product was washed with water and separated. The organic phase was dried over anhydrous Na2SO4 and rotary evaporated. The product was washed with methanol, filtered and dried to obtain a dark purple solid, which was aldehyde porphyrin, denoted as Por-CHO.
[0049] The prepared Por-CHO was subjected to NMR testing, and the results are shown in Figure 2 , where a and b are the H-NMR spectrum and C-NMR spectrum of Por-CHO, respectively.
[0050] Step 2: Preparation of nickel metallated aldehyde porphyrin Por-CHO (200 mg, 0.276 mmol) obtained in step 1 was mixed with nickel acetate (Ni(CH3COO)2, 137.4 mg, 0.55 mmol) and DMF (40 mL), and stirred at 120°C under N2 atmosphere for 4 h. After cooling to room temperature, 160 mL of deionized water was added to precipitate solids, which were filtered and collected. The solids were washed with methanol and dried in vacuo to obtain a dark red product, which was nickel metallated aldehyde porphyrin, recorded as Ni-Por.
[0051] The prepared Ni-Por was subjected to NMR test, and the results are shown in Figure 3 , where a and b are the NMR hydrogen spectrum and NMR carbon spectrum of Ni-Por respectively. 1 In the H NMR spectrum, typical proton signals associated with the porphyrin ring structure can be observed, as well as characteristic peaks of the aldehyde group (-CHO) and the metallated porphyrin center; 13 The C NMR spectrum further provides information about the carbon spectrum of the porphyrin ring, showing characteristic peaks of the carbon of the aldehyde group and the metal-coordinated carbon in the metallated porphyrin. These data indicate that the aldehyde porphyrin binds to the metal ion Ni 2+ With successful coordination, the synthesis of metallated porphyrins is efficient.
[0052] Step 3: Preparation of metalloporphyrin covalent organic framework In an ampoule, the metallated aldehyde porphyrin (69.72 mg, 0.096 mmol), 1,4-phenyldiacetonitrile (PDAN, 30 mg, 0.192 mmol), 1,2-dichlorobenzene (4 mL) and 5 M DBU solution (1,8-diazabicycloundec-7-ene aqueous solution, 0.4 mL) were added, ultrasonicated for 5 min, freeze-thawed for three times, sealed under butane flame vacuum, and heated at 80 ° C for 3 days. The product was washed with dichloromethane, extracted with tetrahydrofuran and dichloromethane for two days, and dried under vacuum at 80 ° C for 12 h to obtain a metal porphyrin covalent organic framework.
[0053] Step 4: Amidoximation of Metalloporphyrin Covalent Organic Framework Take 0.2 g of the metal porphyrin covalent organic framework obtained in step 3 and disperse it in 20 mL of anhydrous ethanol, and ultrasonicate it for 10 min. Add hydroxylamine hydrochloride (NH2OH·HCl, 0.5 g) and triethylamine (N(CH2CH3)3, 3 mL), stir at 85°C for 24 h, and filter. Wash the solid with water, ethanol, and methanol in turn. Then dry it in vacuum at 60°C for 12 h to obtain the amidoximated metal porphyrin covalent organic framework material, which is recorded as Ni-Por-COF.
[0054] Example 2 This embodiment provides an amidoximated metalloporphyrin covalent organic framework material, denoted as Cu-Por-COF.
[0055] The difference between the preparation of this example and that of Example 1 is that in step 2, 0.55 mmol of CuCl2 dihydrate (94 mg) is reacted with 0.276 mmol of Por-CHO to prepare the metallated aldehyde porphyrin. The other steps are the same as those of Example 1, wherein the reaction molar ratio involved in the reaction is the same as that of Example 1.
[0056] The preparation flow chart of this embodiment is as follows Figure 4 shown.
[0057] Example 3 This embodiment provides an amidoximated metalloporphyrin covalent organic framework material, denoted as Co-Por-COF.
[0058] The difference between the preparation of this example and that of Example 1 is that in step 2, 0.55 mmol of CoCl2 is reacted with 0.276 mmol of Por-CHO to prepare the metallated aldehyde porphyrin. The other steps are the same as those of Example 1, wherein the reaction molar ratio involved in the reaction is the same as that of Example 1.
[0059] Performance Characterization (1) The crystal structures of the amidoximated metalloporphyrin covalent organic frameworks synthesized in Examples 1 and 2 were characterized by X-ray diffraction (XRD) technology. Figure 5 .
[0060] Figure 5The XRD patterns of amidoxime Ni porphyrin covalent organic framework (Ni-Por-COF) and amidoxime Cu porphyrin covalent organic framework (Cu-Por-COF) are shown. The XRD patterns show that Ni-Por-COF and Cu-Por-COF have obvious crystal characteristics and clear diffraction peaks, indicating that they have highly ordered structures and good crystal quality. Comparing the different metallized porphyrin frameworks, the XRD patterns show that the diffraction peak positions and intensities of amidoxime Ni-Por-COF and Cu-Por-COF are basically the same, indicating that they have similar crystal structures, but Ni-Por-COF shows a higher diffraction peak intensity, indicating that its crystallinity and order are relatively good.
[0061] (2) The Por-COF, Ni-Por-COF synthesized in Example 1 and the Cu-Por-COF synthesized in Example 2 were subjected to photocurrent test and Mott-Schottky analysis. The results are shown in Figure 6 , where the left picture is the transient photocurrent response result diagram, and the right picture is the Mott-Schottky curve test result diagram. The transient photocurrent test applies light to the surface of different materials, measures their current response, and evaluates the material's photogenerated electron and charge transport capabilities. Through Mott-Schottky analysis, information about the material's carrier concentration, band structure, and semiconductor type can be obtained.
[0062] Figure 6 The left figure shows the transient photocurrent response of Por-COF, Ni-Por-COF, and Cu-Por-COF. The results show that Ni-Por-COF shows the highest transient photocurrent under illumination, indicating that it has the strongest ability to generate and separate photogenerated electrons. In contrast, the transient photocurrents of Cu-Por-COF and Por-COF are lower, indicating that Ni-Por-COF may show better performance in photocatalytic applications. This phenomenon is related to the stronger charge separation and photocatalytic ability of the Ni metallated porphyrin center.
[0063] Figure 6 The figure on the right shows the Mott-Schottky curves of Por-COF, Ni-Por-COF and Cu-Por-COF. The results show that all materials exhibit typical Mott-Schottky curves, proving that these materials have semiconductor properties. In particular, the Mott-Schottky curve of Ni-Por-COF shows that it has a higher electron concentration and a smaller electron migration resistance, indicating that Ni-Por-COF has superior electron conduction properties in the photoelectrocatalytic process. This provides strong support for the application of Ni-Por-COF and Cu-Por-COF in the field of photocatalysis.
[0064] The characterization of step (1) and step (2) shows that the aldehyde porphyrin Por-COF and the metallated porphyrin (Ni-Por-COF and Cu-Por-COF) are successfully synthesized, and the metallated porphyrin covalent organic framework has a good crystal structure, high crystallinity and order. The metallated porphyrin covalent organic framework material of the present invention, especially Ni-Por-COF, has good photoelectric properties and structural stability.
[0065] (3) The Por-COF and Ni-Por-COF synthesized in Example 1, the Cu-Por-COF synthesized in Example 2, and the Co-Por-COF synthesized in Example 3 were used to conduct uranium extraction performance experiments on uranium-containing wastewater.
[0066] Experimental materials and methods: Experimental materials: a standard uranium solution with an initial uranium concentration of 20 ppm, and adsorption materials Por-COF, Ni-Por-COF, Cu-Por-COF, and Co-Por-COF; Experimental conditions: the adsorption performance of the above-mentioned adsorption materials on uranium (U(VI)) was measured under different lighting conditions, where the lighting conditions were divided into two conditions: "dark conditions (no light) and light conditions (simulated sunlight, light source intensity of 100 mW / cm²)", and the experimental temperature was maintained at room temperature (25 ℃); Operation steps: 10 mg of Por-COF, Ni-Por-COF, Cu-Por-COF or Co-Por-COF was added to a solution containing 20 ppm uranium, and an adsorption experiment was carried out. The experiment was stirred continuously for 12 hours under dark conditions and for 20 hours under light conditions. Samples were taken regularly to analyze the changes in uranium concentration in the solution, and the amount of uranium adsorbed was recorded. The maximum adsorption amount q of Por-COF, Ni-Por-COF, Cu-Por-COF and Co-Por-COF max See Table 1. The adsorption amount of uranium at different times for Por-COF, Ni-Por-COF, and Cu-Por-COF is shown in Table 1. Figure 7 , Table 1 and Figure 7 In the figure, Dark means dark conditions, and Light means light conditions.
[0067] Table 1 Adsorption material Maximum adsorption capacity (Dark) Maximum adsorption capacity (Light) Por-COF 74.9 mg / g 114.7 mg / g Ni-Por-COF 219.0 mg / g 335.8 mg / g Cu-Por-COF 208.3 mg / g 291.7 mg / g Co-Por-COF 136.4 mg / g 152.5 mg / g As can be seen from Table 1, the uranium adsorption of Por-COF is low even under illumination, the uranium adsorption of Co-Por-COF is average, and the catalytic ability of Co-Por-COF under dark conditions is not greatly improved, while Cu-Por-COF and Ni-Por-COF both show high adsorption capacity, and the maximum adsorption of Ni-Por-COF reaches 335.8 mg / g. It can be seen that the metallization regulation of aldehyde porphyrin using copper (Cu) or nickel (Ni) has a good effect, which may be related to the effect of the interaction between the outer electron orbit of copper or nickel metal and the π electron system of the porphyrin ring. The interaction between the d orbit of copper or nickel metal and the π electron system of the porphyrin ring can effectively promote the separation of charge carriers and improve the photocatalytic activity of the material. At the same time, copper or nickel metallized porphyrin can enhance its catalytic adsorption ability under dark conditions. Therefore, it is preferred that copper salts and nickel salts are used to metallize porphyrins.
[0068] Figure 7 The adsorption amount of uranium at different times of Por-COF, Ni-Por-COF, and Cu-Por-COF is shown. Figure 7 It can be seen that Ni-Por-COF and Cu-Por-COF both reached adsorption equilibrium within 20 h, indicating that the process has fast adsorption kinetics, and specifically, the adsorption amount increases with time and tends to be stable, showing a good dynamic response; Figure 7 It was confirmed that the adsorption behavior of Por-COF, Ni-Por-COF, and Cu-Por-COF conforms to the pseudo-second-order kinetic equation. The pseudo-second-order kinetic model shows that the adsorption process of uranium is not just physical adsorption, but also involves chemical reactions or other interactions. Adsorption isotherm analysis shows that the adsorption behavior of all materials conforms to the Langmuir isotherm model, further indicating that the adsorption of uranium is a monolayer adsorption and the adsorption sites are uniform.
[0069] And by Figure 7 It can be seen that the adsorption of uranium under light conditions is excellent. Analyzing the reasons, this phenomenon can be attributed to the photocatalytic effect. Under light, the photogenerated electrons interact with the metal d orbital of the metallized porphyrin and the π electron system of the porphyrin ring, effectively promoting the separation and transmission of electrons, thereby enhancing the photocatalytic reduction of U(VI) to insoluble U(IV). In addition, the electron reduction under light not only promotes the conversion of uranium, but also releases additional active sites, further improving the adsorption capacity.
[0070] The uranium extraction performance experiment in step (3) can predict the application prospects of Ni-Por-COF and Cu-Por-COF in extracting uranium from low-concentration uranium-containing wastewater, especially in the fields of nuclear wastewater treatment, mining wastewater recycling and seawater uranium extraction. Figure 8 Schematic diagram showing the application of Ni-Por-COF in low-concentration uranium-containing wastewater. The treatment steps are as follows: Wastewater pretreatment: Uranium-containing wastewater (20 ppm) is firstly subjected to simple filtration or sedimentation to remove some impurities in order to improve the efficiency of the subsequent adsorption process.
[0071] Adsorption process: The pretreated wastewater is mixed with the Ni-Por-COF material and reacted under light conditions. The uranium ions in the wastewater are quickly extracted by utilizing the synergistic effect of adsorption and photocatalysis of the adsorption light-responsive covalent organic framework.
[0072] Extraction of uranium: After a period of reaction, the Ni-Por-COF material adsorbed with uranium is recovered by filtration, and the adsorbed uranium is removed by washing, and finally the uranium-containing material and treated wastewater are obtained.
[0073] Uranium recovery and material regeneration: Uranium can be recovered through simple elution or solvent treatment, and the Ni-Por-COF material can be regenerated and used again for the next round of wastewater treatment.
[0074] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a photoresponsive covalent organic framework material, characterized in that: The following steps are involved: Step S1: reacting aldehyde porphyrin with a metal salt to obtain a metallated aldehyde porphyrin; Step S2: condensing the metallated aldehyde porphyrin with 1,4-benzenediacetonitrile to obtain a metal porphyrin covalent organic framework; Step S3: subjecting the metal porphyrin covalent organic framework to amidoximation reaction to obtain a photoresponsive covalent organic framework material.
2. The preparation method according to claim 1, characterized in that: In step S1, the aldehyde porphyrin is a porphyrin derivative having an aldehyde group.
3. The preparation method according to claim 1, characterized in that: In step S1, the metal salt is a copper salt and / or a nickel salt.
4. The preparation method according to claim 1, 2 or 3, characterized in that: In step S1, the reaction is carried out under an inert gas atmosphere at a reaction temperature of 100-130°C.
5. The preparation method according to claim 1, characterized in that: In step S2, the condensation reaction is carried out under the conditions of a solvent and a catalyst, the solvent is 1,2-dichlorobenzene, and the catalyst is a basic catalyst.
6. The preparation method according to claim 1, characterized in that: In step S3, the metal porphyrin covalent organic framework is subjected to amidoximation reaction with hydroxylamine.
7. The preparation method according to claim 1 or 6, characterized in that: In step S3, the temperature of the amidoximation reaction is 80-100° C., and the reaction time is 20-30 hours.
8. The preparation method according to claim 1 or 6, characterized in that: In step S3, the catalyst for the amidoximation reaction is triethylamine.
9. A photoresponsive covalent organic framework material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the photoresponsive covalent organic framework material prepared by the preparation method according to any one of claims 1 to 8 in uranium extraction.
Citation Information
Patent Citations
Preparation and application of adsorption-photocatalysis type covalent organic framework material
CN115894830A
Two-dimensional metalloporphyrin-based COF (chip on film) material as well as film preparation method and application
CN109467710A
Covalent organic framework material based on metalloporphyrin as well as preparation method and application of covalent organic framework material
CN113563551A
Preparation method and adsorption application of amidoxime functionalized three-dimensional covalent organic framework
CN115677959A
Two-dimensional metalloporphyrin organic framework catalyst as well as preparation method and application thereof
CN118028865A